1979
DOI: 10.1042/bj1810401
|View full text |Cite
|
Sign up to set email alerts
|

The electrophoretically ‘slow’ and ‘fast’ forms of the α2-macroglobulin molecule

Abstract: alpha 2-Macroglobulin (alpha 2M) was isolated from human plasma by a four-step procedure: poly(ethylene glyco) fractionation, gel chromatography, euglobulin precipitation and immunoadsorption. No contaminants were detected in the final preparations by electrophoresis or immunoprecipitation. The protein ran as a single slow band in gel electrophoresis, and was designated 'S-alpha 2M'. S-alpha 2M bound about 2 mol of trypsin/mol. Treatment of S-alpha 2M with a proteinase or ammonium salts produced a form of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
445
2

Year Published

1981
1981
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 524 publications
(473 citation statements)
references
References 41 publications
(40 reference statements)
26
445
2
Order By: Relevance
“…When the proteins were fully denatured and reduced prior to electrophoresis, the reaction with the immobilized proteins was still observed, but at a reduced level. However the electrophoretic migration of the reactive species under these conditions corresponded to an Mr of approximately 170000, consistent with the size of the ot2M subunit and with a smaller Mr protein which may represent a protease-'nicked' form of ~t2 M (Barrett et al, 1979). Thus it appears that the reaction of HAV with ~2M or FCS is not dependent on the quaternary structure of the protein.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…When the proteins were fully denatured and reduced prior to electrophoresis, the reaction with the immobilized proteins was still observed, but at a reduced level. However the electrophoretic migration of the reactive species under these conditions corresponded to an Mr of approximately 170000, consistent with the size of the ot2M subunit and with a smaller Mr protein which may represent a protease-'nicked' form of ~t2 M (Barrett et al, 1979). Thus it appears that the reaction of HAV with ~2M or FCS is not dependent on the quaternary structure of the protein.…”
Section: Discussionmentioning
confidence: 69%
“…When the samples were boiled in SDS and 2-mercaptoethanol prior to electrophoresis, virus still bound to the immobilized proteins. Under these conditions the major reacting species in the FCS lane had an Mr of approximately 170K, which corresponds to the reported size of the ct2M monomer (Barrett et al, 1979). A similar protein could be seen in the fraction 1 sample but virus bound more extensively to a band migrating at approximately 110K, the reported Mr of a proteolytic fragment derived from at2M (Barrett et al, 1979).…”
Section: Western Blotting Of Serum Inhibitory Componentsmentioning
confidence: 72%
See 1 more Smart Citation
“…accumulated knowledge on the trap mechanism, we know that (1) one molecule of tetrameric human c~2M can trap up to two molecules of small proteinases such as chymotrypsin or trypsin, (2) when two mol of chymotrypsin are trapped per mol of c~2M under molar abundance of the former, all four bait regions of tetrameric ~2M are cleaved. The structural changes of CZzM and its homologues that takes place after bait region cleavage can be detected by a variety of physical and biochemical methods including electron microscopy [5,6], X-ray solution scattering [7], circular dichroism [8], electrophoresis [9], gel chromatography [10], fluorescence spectroscopy and sedimentation velocity [11]. We have little information, however, on the kinetic aspects of the reaction such as (1) how fast the bait regions are cleaved after the encounter of ~2 M with proteinases, (2) how many bait regions must be cleaved before the proteinases are trapped, (3) how closely connected in time are the bait region cleavage and the structural change?…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the autolytic cleavage is dependent on the integrity of the internal thiolester. Nucleophile inactivation, autolytic cleavage on denaturation, and the ability to form covalent bonds (with proteases) have also been described for a2-macroglobulin (a2M) (25)(26)(27)(28)(29)(30)(31). We and others have shown that nucleophile inactivation again correlates with the appearance of a thiol group (10,(32)(33)(34).…”
mentioning
confidence: 99%